2014
DOI: 10.1021/ja505618n
|View full text |Cite
|
Sign up to set email alerts
|

Dipole-Mediated Rectification of Intramolecular Photoinduced Charge Separation and Charge Recombination

Abstract: Controlling charge transfer at a molecular scale is critical for efficient light harvesting, energy conversion, and nanoelectronics. Dipole-polarization electrets, the electrostatic analogue of magnets, provide a means for "steering" electron transduction via the local electric fields generated by their permanent electric dipoles. Here, we describe the first demonstration of the utility of anthranilamides, moieties with ordered dipoles, for controlling intramolecular charge transfer. Donor− acceptor dyads, eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
95
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 51 publications
(99 citation statements)
references
References 73 publications
4
95
0
Order By: Relevance
“…1). In addition to determining that these oligomers of aromatic orthoamino acids are indeed molecular electrets [46], we also demonstrated that the Aa dipole rectifies charge transfer [45]. Furthermore, derivatizing an anthranilamide with a secondary amine as R 2 at the 5 th position ( Fig.…”
Section: Introductionsupporting
confidence: 52%
See 4 more Smart Citations
“…1). In addition to determining that these oligomers of aromatic orthoamino acids are indeed molecular electrets [46], we also demonstrated that the Aa dipole rectifies charge transfer [45]. Furthermore, derivatizing an anthranilamide with a secondary amine as R 2 at the 5 th position ( Fig.…”
Section: Introductionsupporting
confidence: 52%
“…Each Aa residue is added to the sequence as a 2-nitrobenzoic acid derivative [45,46]. A selective reduction of the nitro group to amine prepares the thus added N-terminal residue for the next amide-coupling step [46].…”
Section: Preparation Of the Anthranilamide Residuesmentioning
confidence: 99%
See 3 more Smart Citations